Lessons from the Old Masters on Assessing Equity and Efficiency : A Primer for Fiscal Policymakers - Gaspar, Vitor; Mauro, Paolo; Poghosyan, Tigran (Washington, D.C. : International Monetary Fund, 2017)
How can a society's well-being be measured to include not only average incomes but also their distribution? How can the effects of policies be assessed by considering both equity and efficiency? This primer outlines the seminal contributions of influential economists of the past, including Arthur Okun, who developed a simple method to elicit people's preferences regarding redistribution, and Anthony Atkinson, who showed how equity and efficiency can be measured simultaneously and summarized in a single, intuitive index expressed in monetary units (such as dollars). These methods are applied to recent data to gauge how countries fare when both mean incomes and their distribution are considered together, and to a hypothetical tax-and-transfer scheme assessed through a general equilibrium model for household-level data.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet